2019
DOI: 10.47723/kcmj.v13i2.108
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of antibiotics in AL-Elwia Pediatric Teaching Hospital, Baghdad, 2016.

Abstract: Background: Antibiotics are among the most commonly used medicine, in both community and hospital setting, all over the world especially in countries where no strict guideline to regulate their use. In Iraq, only a few studies conducted to describe the antibiotic prescription pattern in general hospitalsand even less in pediatric hospital. Objective: To describe the patterns for antibiotics used in Elwia pediatric teaching hospital in Baghdad, Iraq Type of the study: Descriptive cross sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The rising in resistance rate to previously effective antibiotics may be due to uncontrolled usage of prescription only medication including antibiotics and steroids in private settings (15,38,39) , and even due to irrational antibiotics prescribing practice (40)(41)(42)(43)(44) .…”
Section: Discussionmentioning
confidence: 99%
“…The rising in resistance rate to previously effective antibiotics may be due to uncontrolled usage of prescription only medication including antibiotics and steroids in private settings (15,38,39) , and even due to irrational antibiotics prescribing practice (40)(41)(42)(43)(44) .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained from other studies in Baghdad, Iraq and India, where gastroenteritis and respiratory tract infections were the most commonly reported diagnoses. 12,20 Regarding the type of antibiotics prescribed, amoxicillin, ceftriaxone and gentamicin were the most commonly prescribed drugs (Table 2). These are broad spectrum antibiotics and frequently used as empiric therapy, which could explain the obtained results.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, a study conducted in Al-Elwia Pediatric Teaching Hospital in Baghdad has shown that 87.56% of the patients who visited the hospital have received antibiotics, and amoxicillin was the antibiotic preferred by pediatricians. 12 Another study that surveyed five teaching hospitals in Baghdad has found that 66.7% of patients were treated with at least one antimicrobial agent and the neonatal intensive care unit had the highest antimicrobial prescription rate (97.2%) where ceftriaxone was the most frequently used antibiotic. 13 Clinical pharmacist intervention (CPI) is one of the most important interventions used to optimize medication prescription, prevent drug-related issues and lower drug costs for both the patient and the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…3-Pharmacies must engage in a mandatory continuous medical education programs to improve and update their clinical and practice skills [6] . 4-Disseminating the culture of proper antibiotics use by healthcare providers to raise public awareness and conducting public educational programs through mass media [14] . 5-Educate health care by using seminars or any other educational means [10 ].…”
Section: Recommendation and Interventions For Antibiotics Misusementioning
confidence: 99%
“…Self-medication with antibiotics is a worldwide problem, not only in the developing countries but also in the developed countries [5] . Studies among Iraqi population have reported prevalence of improper use of antibiotic [6][7][8][9][10][11][12][13][14] , this will lead to increase in the health problems.…”
Section: Introductionmentioning
confidence: 99%